2015
DOI: 10.1111/1365-2435.12465
|View full text |Cite
|
Sign up to set email alerts
|

Birth date predicts alternative life‐history pathways in a fish with sequential reproductive tactics

Abstract: Summary In species with plastic expression of alternative reproductive tactics (ARTs), individuals of the same sex, usually males, can adopt different reproductive tactics depending on factors such as body size. The ‘birth date hypothesis’ proposes that condition‐dependent expression of ARTs may ultimately depend on birth date, because individuals born at different times of the year may achieve different sizes and express different reproductive tactics accordingly. However, this has rarely been tested. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…We, however, only found a small proportion of intermediates (9%). Fagundes et al [46] also found a small proportion of intermediates or transient individuals (7%) in Peacock Blenny, Salaria pavo . In this long-term mark-recapture study, it was found that intermediates express a sneaker tactic and switch to the nest-holder or parental tactic within their first breeding season [46].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We, however, only found a small proportion of intermediates (9%). Fagundes et al [46] also found a small proportion of intermediates or transient individuals (7%) in Peacock Blenny, Salaria pavo . In this long-term mark-recapture study, it was found that intermediates express a sneaker tactic and switch to the nest-holder or parental tactic within their first breeding season [46].…”
Section: Discussionmentioning
confidence: 97%
“…Fagundes et al [46] also found a small proportion of intermediates or transient individuals (7%) in Peacock Blenny, Salaria pavo . In this long-term mark-recapture study, it was found that intermediates express a sneaker tactic and switch to the nest-holder or parental tactic within their first breeding season [46]. While we cannot tell when tactics are fixed, because we did not follow fish for any length of time, our data do suggest that tactics in the Round Goby are fixed before the breeding season.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Examples exist across varied taxa and parity modes, including an association of early birthdate with adoption of an alternative reproductive tactic in male fish (Fagundes et al, 2015), with greater survival and larger mass at first summer's end in penguin chicks (Stier et al, 2014), and with greater survival (at high population density) in squirrels (Williams et al, 2014). In principle, effects on offspring from time of birth may arise from: (1) seasonal variation in the quality of the environment into which offspring are born; (2) variation in the quality of offspring themselves, arising from prenatal developmental effects; and (3) in those species that provide it, variation in parental care during the postnatal period (Wapstra et al, 2010;Stier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%